A method of preparation and pulse electrolysis based on a self-supporting copper-based catalyst
Patent Information
- Application Number
- CN202311466399.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-11-07
AI Technical Summary
常用的制备方法如水热、溶剂热等由于反应时间长、难以控制反应条件等缺点存在一些局限性,故而开发更加简单便捷的合成方法用于制备高效稳定的催化剂对提升合成氨效率至关重要
(1)采用电化学阳极氧化法和退火在泡沫铜基底上合成自支撑CuxO纳米线催化剂,该方法简单便捷,成本较低,有利于工业化生产。
Smart Images

Figure CN117488338B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of catalyst preparation and electrochemical technology for energy and the environment, specifically to a method for preparing a self-supporting copper-based catalyst and pulse electrolysis. Background Technology
[0002] Ammonia (NH3) plays a vital role in modern society, not only in the production of fertilizers and chemical raw materials, but also as an energy storage carrier, potentially becoming a substitute for fossil fuels. Traditional ammonia production mainly relies on the Haber process, which synthesizes ammonia from nitrogen and hydrogen under high temperature and pressure with an iron or ruthenium-based catalyst. Due to the high emissions and energy consumption of this process, novel electrocatalytic nitrogen-to-ammonia technology has been developed. However, the bond energy of the nitrogen-nitrogen triple bond is as high as 941 kJ / mol. -1 Furthermore, its low solubility in water poses a significant challenge to the yield and selectivity of nitrogen reduction for ammonia synthesis. Therefore, nitrite (NO2) was chosen as the preferred alternative. - As a more easily reduced soluble nitrogen source, NO2 can optimize the performance of electrochemical ammonia synthesis. Meanwhile, toxic NO2... - Nitrite is a common pollutant in surface and groundwater, which can easily cause diseases such as methemoglobinemia and cancer. Nitrite reduction to synthesize ammonia can not only provide a green and sustainable ammonia synthesis technology, but also alleviate global energy and pollution problems.
[0003] Currently, some noble and non-noble metal materials have been applied to nitrite reduction reactions, among which copper-based catalysts have attracted widespread attention due to their unique properties. However, cuprous oxide and metallic copper are easily oxidized upon contact with air, and both copper oxide and cuprous oxide are reduced to elemental copper under reducing current. Therefore, how to stably maintain a large number of highly active copper sites during long-term electrochemical reactions is an urgent problem that needs to be solved.
[0004] In addition to the intrinsic activity of the catalyst, the morphology and structural design of the material are also crucial. Nanowire array structures have a large specific surface area, exposing more active sites, which is beneficial for ion and electron transport and effectively improves the catalytic activity of the electrode. Commonly used preparation methods such as hydrothermal and solvothermal methods have limitations due to long reaction times and difficulty in controlling reaction conditions. Therefore, developing simpler and more convenient synthesis methods for preparing efficient and stable catalysts is essential for improving the efficiency of ammonia synthesis. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of the embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0006] In view of the problems existing in the preparation of the above and / or existing catalysts and in the electrochemistry of energy and the environment, the present invention is proposed.
[0007] Therefore, the purpose of this invention is to provide a method for the preparation and pulse electrolysis of a self-supporting copper-based catalyst. This method is simple and controllable, and the prepared copper-based catalyst exposes a large number of active sites. At the same time, the active phase of cuprous oxide is stabilized by pulse electrolysis, which is beneficial to the efficient and green synthesis of ammonia and improves the yield and selectivity of ammonia synthesis.
[0008] To address the aforementioned technical problems, according to one aspect of the present invention, the present invention provides the following technical solution: A method for preparing and pulse electrolyzing a self-supporting copper-based catalyst includes the following steps: Step 1: Immerse the copper foam in 1 M hydrochloric acid solution and sonicate for 5-20 min to remove surface oxides. Then, clean it with deionized water, acetone, and anhydrous ethanol in sequence using ultrasonic cleaning. After vacuum drying in a 40 ℃ oven, seal and store it. Step 2: Using the anodic oxidation method, the copper foam substrate is oxidized in NaOH electrolyte solution to grow Cu(OH)2 nanowires in situ on its surface. After completion, it is rinsed with deionized water and anhydrous ethanol in sequence, and then vacuum dried. Step 3: Place the copper foam electrode with Cu(OH)2 coating on its surface into a muffle furnace and calcine it at 200-400 °C for 2-4 hours, with a heating rate of 5 °C / min. -1 To obtain self-supporting Cu x O nanowire electrode, the Cu x Copper in O exists in a mixed valence state of 0, +1, and +2.
[0009] As a preferred embodiment of the preparation method of a self-supporting copper-based catalyst described in this invention, in step two, oxidation is carried out in a 1-3 M NaOH solution, using the copper foam treated in step one as the working electrode, a platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode.
[0010] In a preferred embodiment of the preparation method of a self-supporting copper-based catalyst described in this invention, in step two, an oxidation current of 20-40 mA cm⁻² is applied to the working electrode for an oxidation time of 10-30 min.
[0011] A self-supporting copper-based catalyst prepared by the method described above.
[0012] Preferably, the method is as follows: self-supporting Cu x The O electrode is used as the working electrode, and a three-electrode system is used to perform pulsed electrolysis in the electrolyte. A pulsed potential is periodically applied to make Cu... x The O electrode generates more cuprous oxide during electrolysis.
[0013] Preferably, the method is as follows: the three-electrode system uses self-supporting Cu... x The O electrode is used as the working electrode, the platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode.
[0014] Preferably, the method is as follows: the pulse electrolysis is carried out in an H-type electrolytic cell, the cathode electrolyte is a 1M NaOH solution containing 10~100mM NO2-, and the anode electrolyte is a 1M NaOH solution.
[0015] Preferably, the method is as follows: the applied potential of the pulse electrolysis oscillates periodically between the open circuit potential and the cathode potential, the cathode potential is set to -0.4~-0.8V vs. RHE, the pulse width in the pulse electrolysis is 0.5~10s, and the duty cycle is 50%.
[0016] Preferably, the method is as follows: during pulse electrolysis, by setting the optimal pulse parameters, a large number of stable cuprous oxide active sites can be obtained.
[0017] Based on the above-mentioned application of the pulse electrolysis method based on self-supporting copper-based catalyst in the field of ammonia synthesis, pulse electrolysis is used for the electrochemical reduction of nitrite to synthesize ammonia. Compared with traditional constant potential electrolysis, it effectively improves the rate and selectivity of ammonia synthesis.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) Self-supporting Cu was synthesized on a copper foam substrate by electrochemical anodizing and annealing. x O nanowire catalysts: This method is simple, convenient, and low-cost, which is conducive to industrial production.
[0019] (2) Utilizing the prepared self-supporting Cu x O nanowire catalysts were used for pulsed electrolysis and the electrochemical reduction of nitrite to synthesize ammonia, which controllably altered the Cu content. x By adjusting the ratio of copper oxide, cuprous oxide, and metallic copper in the electrolyte and regulating the pulse parameters, a large amount of stable cuprous oxide, a favorable active phase, was obtained, which effectively improved the yield and selectivity of electrocatalytic ammonia synthesis. NO2 in the electrolyte... -At a concentration of 0.25 mM, the ammonia yield by pulse electrolysis at a potential of -0.7 V vs. RHE can reach 115.1 mg h⁻¹. -1 cm -2 The corresponding Faraday efficiency is 91.1%, which is better than the performance of traditional constant potential electrolysis under the same conditions.
[0020] In summary, the method provided by this invention synthesizes self-supporting Cu. x The O nanowire catalyst, with the increased proportion of cuprous oxide active phase achieved by pulse electrolysis technology, enables the degradation of nitrite and the efficient electrochemical synthesis of ammonia, and is expected to be applied on a large scale in industrial production. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 This is a schematic diagram illustrating the preparation of the self-supporting copper-based catalyst and the application of the pulse electrolysis method in the electrocatalytic synthesis of ammonia.
[0022] Figure 2 Self-supporting Cu prepared in Example 1 x X-ray diffraction pattern of O nanowire catalyst; Figure 3 (a) Self-supporting Cu in Example 1 x X-ray photoelectron spectroscopy of Cu 2p catalyst in O nanowire catalyst, (b) is the self-supporting Cu in Example 1. x Auger electron spectroscopy of Cu LMM for O nanowire catalysts; Figure 4 Self-supporting Cu in Example 1 x Scanning electron microscope image of O nanowire catalyst; Figure 5 (a) Self-supporting Cu in Example 4 x The graph shows the change in ammonia yield of the O nanowire catalyst with cathode potential. (b) shows the Cu nanowire catalyst in Example 4. x The Faraday efficiency of O nanowire catalyst as a function of cathode potential; Figure 6 (a) Self-supporting Cu after reaction in Example 4 x X-ray photoelectron spectroscopy of Cu 2p in O nanowire catalyst, (b) is the self-supporting Cu after the reaction in Example 1. x Auger electron spectroscopy of CuLMM catalyst with O nanowires; Figure 7 (a) Self-supporting Cu after reaction in Example 5 x X-ray photoelectron spectroscopy of Cu 2p catalyst using O nanowires, (b) showing the self-supporting Cu after the reaction in Example 5. x Auger electron spectroscopy of Cu LMM for O nanowire catalysts; Figure 8 (a) Self-supporting Cu after reaction in Example 6 x X-ray photoelectron spectroscopy of Cu2p catalyst using O nanowires (b) shows the self-supporting Cu after the reaction in Example 6. x Auger electron spectroscopy of Cu LMM for O nanowire catalysts; Figure 9 (a) Self-supporting Cu in Comparative Example 1 x The graph shows the ammonia yield of the O nanowire catalyst as a function of cathode potential. (b) shows the Cu content in Comparative Example 1. x The Faraday efficiency of O nanowire catalyst as a function of cathode potential; Figure 10 (a) Self-supporting Cu after reaction in Comparative Example 1 x X-ray photoelectron spectroscopy of Cu 2p in O nanowire catalyst (b) shows the self-supported Cu after reaction in Comparative Example 1. x Auger electron spectroscopy of Cu LMM for O nanowire catalysts. Detailed Implementation
[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0024] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0025] Secondly, the present invention is described in detail with reference to the schematic diagrams. When detailing the embodiments of the present invention, for ease of explanation, the cross-sectional views illustrating the device structure may be partially enlarged, not according to the usual scale. Furthermore, the schematic diagrams are merely examples and should not limit the scope of protection of the present invention. In addition, actual fabrication should include three-dimensional spatial dimensions of length, width, and depth.
[0026] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.
[0027] This invention provides a method for preparing a self-supporting copper-based catalyst and performing pulse electrolysis. This method is simple and controllable, and the prepared copper-based catalyst exposes a large number of active sites. Simultaneously, pulse electrolysis stabilizes the cuprous oxide active phase, which is beneficial for the efficient and green synthesis of ammonia, improving the yield and selectivity of ammonia synthesis. Please refer to [link to relevant documentation]. Figures 1-10 The following are examples: Example 1 S1. Soak the copper foam in 1 M hydrochloric acid solution and sonicate for 10 min to remove surface oxides. Then, clean it with deionized water, acetone and anhydrous ethanol in sequence. After vacuum drying in an oven at 40℃, seal and store. S2. Using the cleaned copper foam as the working electrode and a platinum mesh as the counter electrode, the copper foam substrate was oxidized in a 3 M NaOH electrolyte solution using anodizing with Ag / AgCl / saturated KCl as the reference electrode, and a current density of 30 mA cm⁻¹ was applied. -2 The oxidation time was 20 min to grow Cu(OH)2 nanowires in situ on its surface. After the oxidation was completed, it was rinsed with deionized water and anhydrous ethanol in sequence, and then vacuum dried. S3. Place the copper foam electrode with Cu(OH)2 coating on its surface into a muffle furnace and calcine it at 300℃ for 2 hours, with a heating rate of 5℃ / min. -1 To obtain self-supporting Cu x O nanowire electrode.
[0028] Self-supporting Cu prepared using the method of Example 1 x Using O nanowire electrodes as samples, X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and Auger electron spectroscopy (AES) were performed. Results are attached. Figure 2-4 As shown: 1) Reference Figure 2 X-ray diffraction (XRD) analysis results show that the prepared self-supporting Cu x In addition to the copper substrate, the O nanowire catalyst also contains a mixed phase of copper oxide and cuprous oxide. 2) Reference Figure 3 X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES) results showed that copper exists in a mixed valence state of 0, +1, and +2. The prepared self-supporting Cu... x O catalysts exhibit multiple coexisting valence states; 3) Reference Figure 4 Scanning electron microscopy (SEM) results show that Cu x O nanowires with a length of 10~20μm and a diameter of 50~200nm are uniformly covered on the surface of copper foam.
[0029] Example 2 S1. Soak the copper foam in 1 M hydrochloric acid solution and sonicate for 10 min to remove surface oxides. Then, clean it with deionized water, acetone and anhydrous ethanol in sequence. After vacuum drying in an oven at 40℃, seal and store. S2. Using the cleaned copper foam as the working electrode and a platinum mesh as the counter electrode, the copper foam substrate was oxidized in a 3 M NaOH electrolyte solution using anodizing with Ag / AgCl / saturated KCl as the reference electrode. A current density of 20 mA cm⁻¹ was applied. -2 The oxidation time was 30 min to grow Cu(OH)2 nanowires in situ on its surface. After the oxidation was completed, it was rinsed with deionized water and anhydrous ethanol in sequence, and then vacuum dried. S3. Place the copper foam electrode with Cu(OH)2 coating on its surface into a muffle furnace and calcine it at 200℃ for 2 hours, with a heating rate of 5℃ / min. -1 To obtain self-supporting Cu x O nanowire electrode.
[0030] Example 3 S1. Soak the copper foam in 1M hydrochloric acid solution and sonicate for 10 minutes to remove surface oxides. Then, clean it with deionized water, acetone and anhydrous ethanol in sequence. After vacuum drying in an oven at 40℃, seal and store. S2. Using the cleaned copper foam as the working electrode and a platinum mesh as the counter electrode, the copper foam substrate was oxidized in a 3 M NaOH electrolyte solution using anodizing with Ag / AgCl / saturated KCl as the reference electrode, and a current density of 40 mA cm⁻¹ was applied. -2 The oxidation time was 10 min to grow Cu(OH)2 nanowires in situ on its surface. After the oxidation was completed, it was rinsed with deionized water and anhydrous ethanol in sequence, and then vacuum dried. S3. Place the copper foam electrode with Cu(OH)2 coating on its surface into a muffle furnace and calcine it at 500℃ for 2 hours, with a heating rate of 5℃ / min. -1 To obtain self-supporting Cu x O nanowire electrode.
[0031] Example 4 The self-supporting Cu prepared in Example 1 x O catalyst was used as the working electrode, platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode. Pulse electrolysis was performed in an H-type electrolytic cell. The cathode electrolyte contained 25 mM NO2. -A 1 M NaOH solution was used as the anolyte, and open-circuit and cathode potentials were applied periodically. Each potential had the same dwell time (50% duty cycle) and a pulse width of 1 s. The cathode potential ranged from -0.4 to -0.8 V vs. RHE. The total electrolysis time was 1 h (including the open-circuit potential). The generated ammonia was detected using the indophenol blue colorimetric method, and the absorbance was measured using a UV-Vis spectrophotometer. The ammonia yield was calculated using a standard ammonium chloride solution. The ammonia synthesis performance under these conditions was as follows: Figure 5 As shown, the highest ammonia yield of 115.1 mg h was obtained at a potential of -0.7 V vs. RHE. -1 cm -2 The corresponding Faraday efficiency is 91.1%.
[0032] Self-supporting Cu after pulse electrolysis at -0.7 V vs. RHE potential using the method of Example 4 x Using O nanowire electrodes as samples, X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES) were performed. The results are attached. Figure 6 As shown, the proportions of copper oxide, cuprous oxide, and metallic copper change, with cuprous oxide becoming the main component.
[0033] Example 5 The self-supporting Cu prepared in Example 1 x O catalyst was used as the working electrode, platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode. Pulse electrolysis was performed in an H-type electrolytic cell. The cathode electrolyte contained 25 mM NO2. - The anolyte was a 1 M NaOH solution. The open circuit potential and the cathode potential were applied periodically. The dwell time of each potential was the same, i.e., the duty cycle was 50%, the pulse width was 0.5 s, the cathode potential was -0.7 V vs. RHE, and the total electrolysis time was 1 h (including the open circuit potential).
[0034] Self-supporting Cu after pulse electrolysis under these conditions x Using O nanowire electrodes as samples, X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES) were performed. The results are attached. Figure 7 As shown, the ratio of copper oxide, cuprous oxide, and metallic copper changed, and the contents of cuprous oxide and metallic copper increased compared to before electrolysis.
[0035] Example 6 The self-supporting Cu prepared in Example 1 x O catalyst was used as the working electrode, platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode. Pulse electrolysis was performed in an H-type electrolytic cell. The cathode electrolyte contained 25 mM NO2. -The 1 M NaOH solution was used as the anolyte, and the open circuit potential and cathode potential were applied periodically. The dwell time of each potential was the same, i.e., the duty cycle was 50%, the pulse width was 10s, the cathode potential was -0.7 V vs. RHE, and the total electrolysis time was 1h (including the open circuit potential).
[0036] Self-supporting Cu after pulse electrolysis under these conditions x Using O nanowire electrodes as samples, X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES) were performed. The results are attached. Figure 8 As shown, the ratio of copper oxide, cuprous oxide, and metallic copper changed, with the metallic copper content increasing significantly compared to before electrolysis, and the cuprous oxide content partially increasing.
[0037] Comparative Example 1 The self-supporting Cu prepared in Example 1 x O catalyst was used as the working electrode, platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode. Pulse electrolysis was performed in an H-type electrolytic cell. The cathode electrolyte contained 25 mM NO2. - A 1 M NaOH solution was used as the anolyte, and a conventional constant-potential electrolysis reaction was performed for 1 hour at an electrolysis potential of -0.4 to -0.8 V vs. RHE. The generated ammonia was detected using the indophenol blue colorimetric method, and the absorbance was measured using a UV-Vis spectrophotometer. The ammonia synthesis yield was calculated using a standard ammonium chloride solution. The ammonia synthesis performance under these conditions is as follows: Figure 9 As shown, the ammonia yield obtained at -0.7V vs. RHE potential was 79.5 mgh. -1 cm -2 The corresponding Faraday efficiency is 84.8%.
[0038] The results of Comparative Example 1 and Example 4 (e.g.) Figure 5 As shown, the highest ammonia yield of 115.1 mg h was obtained at a cathode potential of -0.7 V vs. RHE. -1 cm -2 Compared to the self-supporting Cu in Example 4 (with a corresponding Faraday efficiency of 91.1%), the efficiency of the self-supporting Cu in Example 4 is significantly lower. x The ammonia yield and Faraday efficiency of the pulse electrolysis method using O catalyst are significantly better than those of conventional constant potential electrolysis, further demonstrating the advantages of the pulse electrolysis method of the present invention.
[0039] Self-supporting Cu after potentiostatic electrolysis at -0.7 V vs. RHE using the method of Comparative Example 1 x Using O nanowire electrodes as samples, X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES) were performed. The results are attached. Figure 10 As shown, the proportions of copper oxide, cuprous oxide, and metallic copper change, with metallic copper becoming the main component.
[0040] Although the present invention has been described above with reference to embodiments, various modifications can be made and components can be replaced with equivalents without departing from the scope of the invention. In particular, as long as there is no structural conflict, the features in the disclosed embodiments can be combined with each other in any manner. The lack of an exhaustive description of these combinations in this specification is merely for the sake of brevity and resource conservation. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a self-supporting copper-based catalyst, characterized in that, Includes the following steps: Step 1: Immerse the copper foam in 1 M hydrochloric acid solution and sonicate for 5-20 min to remove surface oxides. Then, clean it with deionized water, acetone, and anhydrous ethanol in sequence using ultrasonic cleaning. After vacuum drying in a 40 ℃ oven, seal and store it. Step 2: Using the anodic oxidation method, the copper foam substrate is oxidized in NaOH electrolyte solution to grow Cu(OH)2 nanowires in situ on its surface. After completion, it is rinsed with deionized water and anhydrous ethanol in sequence, and then vacuum dried. Step 3: Place the copper foam electrode with Cu(OH)2 coating on its surface into a muffle furnace and calcine it at 200-400 °C for 2-4 hours, with a heating rate of 5 °C / min. -1 To obtain self-supporting Cu x O nanowire electrode.
2. The method for preparing a self-supporting copper-based catalyst according to claim 1, characterized in that, Step two involves oxidation in a 1-3 M NaOH solution, using the copper foam treated in step one as the working electrode, a platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode. The Cu... x Copper in O exists in a mixed valence state of 0, +1, and +2.
3. The method for preparing a self-supporting copper-based catalyst according to claim 1, characterized in that, In step two, a 20-40 mA cm⁻¹ pressure is applied to the working electrode. -2 Oxidation current, oxidation time is 10~30 min.
4. A self-supporting copper-based catalyst prepared by the method of claim 1.
5. The pulse electrolysis method for a self-supporting copper-based catalyst according to claim 4, characterized in that, The method is as follows: self-supporting Cu x The O electrode is used as the working electrode, and a three-electrode system is used to perform pulsed electrolysis in the electrolyte. A pulsed potential is periodically applied to make Cu... x The O electrode generates more cuprous oxide during electrolysis.
6. The pulse electrolysis method for a self-supporting copper-based catalyst according to claim 5, characterized in that: The three-electrode system is respectively based on self-supporting Cu x The O electrode is used as the working electrode, the platinum mesh as the counter electrode, and Ag / AgCl / saturated KCl as the reference electrode.
7. The pulse electrolysis method for a self-supporting copper-based catalyst according to claim 5, characterized in that: The pulse electrolysis is carried out in an H-type electrolytic cell, and the cathode electrolyte contains 10~100 mM NO2. - The anolyte is a 1M NaOH solution.
8. The pulse electrolysis method for a self-supporting copper-based catalyst according to claim 5, characterized in that: The applied potential of the pulse electrolysis oscillates periodically between the open circuit potential and the cathode potential. The cathode potential is set to -0.4 to -0.8 V vs. RHE. The pulse width in the pulse electrolysis is 0.5 to 10 s, and the duty cycle is 50%.